Effects of spacing and herbaceous hydroseeding on water stress exposure and root development of poplars planted in soil-covered waste rock slopes. Issue 2 (3rd April 2019) - Babi, Khadija; Guittonny, Marie; Larocque, Guy R.; Bussière, Bruno
ABSTRACT: Root development is important to ensure tree survival in conditions of water stress. Despite their long-recognized role, little attention has been given to their development on waste rock slopes subject to rapid drainage. This study was conducted in an open-pit gold mine in a boreal forest. Its main objective was to establish a plantation design with a moderate level of competition for water resources on a waste rock slope. A hybrid poplar plantation was established in May 2013 on a soil-covered waste rock slope of 33%. The experimental design included three different poplar spacings: 1 × 1 m, 2 × 2 m without herbaceous seeding, 2 × 2 m with herbaceous seeding and 4 × 4 m. The poplars responded to increased competition resulting from closer spacing and herbaceous seeding by investing less energy in diameter and height growth. Poplar individuals that were subject to high levels of competition were able to acclimatize to water stress conditions by increasing root length density and specific root length and by reducing above-ground biomass. This study indicates that some clones of hybrid poplar showing phenotypic plasticity in the ratio of above- and belowground growth can be adapted for short-term revegetation of mine sites.